Time of Day Influences Psychophysical Measures in Women With Burning Mouth Syndrome - Payano Sosa, Janell S.; Da Silva, Joyce T.; Burrowes, Shana A. B.; Yoo, Soo Y.; Keaser, Michael L.; Meiller, Timothy F.; Seminowicz, David A. (Frontiers in Neuroscience, 2021)
Burning mouth syndrome (BMS) is a chronic orofacial pain condition that mainly affects postmenopausal women. BMS type I patients report little to no spontaneous pain in the morning and increases in pain through the day, peaking in the afternoon. Quantitative sensory testing (QST) findings from BMS type 1 patients are inconsistent as they fail to capture this temporal variation. We examined how QST in BMS type 1 (n=18) compared to healthy participants (n=33) was affected by time of day. QST of the face and forearm included warmth detection threshold (WDT), cold detection threshold (CDT), and heat pain thresholds (HPT), ratings of suprathreshold heat, and pressure pain thresholds (PPT), and was performed twice: once in the morning and once in the afternoon. Compared to healthy participants, BMS patients had higher pain sensitivity to phasic heat stimuli at most temperatures (35°C U=126.5, p=0.0006, 39°C U=186.5, p=0.0386, 41°C U=187.5, p=0.0412, 43°C U=171, p=0.0167, 45°C U=168.5, p=0.0146) on the forearm, but no differences in pain thresholds (HPT and PPT) regardless of time of day or body area tested. BMS patients had higher WDT (U= 123, p=0.0172), and lower CDT (U= 98, p=0.0021) of the forearm and lower WDT of the face (U=55, p=0.0494). The differences in forearm WDT (U= 71.5, p=0.0113) and CDT (U= 70, p=0.0096) were most pronounced in the morning. In summary, BMS type I patients had increased pain sensitivity on the forearm, but no differences in pain thresholds on the face or forearm. Patients also showed altered thermal sensitivity, which depended on body area tested (heightened in the orofacial region but blunted on the forearm), and was more pronounced in the morning plausibly due to hypervigilance.